TRAINING AS A FORM OF PROFESSIONAL SELF-IMPROVEMENT OF THE EDUCATIONAL MANAGER - Hladkova, Valentina (Educological discourse, 2018)
Internship is a form of advanced training. In the system of advanced training, modern pedagogical technologies are used. Such technologies are based on the trained independent work of the students in the conditions of wide use of the Internet. It is proposed to introduce into the existing curricula for the training of additional special courses (additional module) "Akmeologiya management education institution". The result of mastering this module is the construction of a cadet own progressive trajectory of professional self-improvement (pragmatic result) and readiness for its practical implementation (psychological result). Improvement of the qualifications of the educational staff should be carried out in the form of internship using permanent and distance form. The general internship program for this contingent of employees involves three phases - appointment, work and final. The theoretical material is processed in eyeglass lectures-presentations and seminars. At the same time, it provides significant assistance in business and quasi-professional games. At the end of the introductory phase of the internship, the choice of the theme for an individual-creative task is carried out. During the next working phase, each trainee prepares an individual creative work according to the chosen topic. Such a task may be the social-organizational project of organization development, the author’s program of self-development (self-realization), etc. Work on individual and creative tasks is carried out in correspondence mode. It can dial distance and involves coaching. The formation of the ability to personally-professional self-development contributes to the use of acmeological technologies. The possibility of formation of acmeological competence is considered. One of the forms of such technology is acmeological training. The final stage in the formation of the acmeological competence of the educational institution manager is the acme-synergetic accompaniment.